Northwest History. Forest Fires (Cont'd). (1935)
Forest Blazes Under Control. Forest Blazes Under Control. Although numerous new fires were reported in scattered sections of the Pacific northwest, forest service and other fighters held their own on major blazes today. With one exception, fighting crews reported they had controlled the larger blazes, scattered from the Pacific coast to Montana and Wyoming. Fire conditions grew steadily worse throughout the area, however, with humidity low and high temperatures searing the timberlands, says an Associated Press summary of the situation. McCall Fire Still Raging. The only major outbreak out of control was the 14,000-acre Idaho national forest fire, northeast of McCall, in central Idaho. More than 800 men struggled through the night to trench it, but it remained out of bounds. A new fire roared through a tourist camp, destroying all cabins and other facilities and consuming about 150 acres of timber between St. Regis and Superior, Mont. This blaze and nine others in region No. 1, including western Montana, north Idaho and eastern Washington, were checked. The other blazes were west and southwest of Missoula, Mont. The Waterton, lakes fire, on the north border of Glacier National park in Canada, was subsided after burning 1500 acres. Another fire on Kennedy creek also was checked. Washington Blazes Small. Western Washington, where numerous slashing and timber fires have been reported, remained free of larger blazes today. In the Grays Harbor region 30 fighters were kept on a 200-acre burn in second growth timber in the Satsop valley, and 40 men were battling a blaze on state timber in the Kamilchie valley. A new fire was being investigated by fire wardens on the lower North river. All other fires were under control. The Shoshone National forest fire in northwestern Wyoming defied 500 fighters last night, after having consumed 10,000 acres of pine timber.